Patterns of Conversion from Christianity to Islam in the Middle East During the Early Rise of Islam (7th – 8th Centuries) and Its Implications for Christians in Indonesia - Yoanes Sinaga; Zainal Sibagariang (Fakultas Filsafat Universitas Advent Indonesia, 2026)
This study investigates the conversions from Christianity to Islam during the 7th–8th century in the Middle East and their ramifications for contemporary Indonesian Christian communities contending with minority status in a Muslim-majority nation. Applying a framework that is both historical and missiological, it contrasts historical trends that are driven by social mobility, economic incentives, theological resilience, and cultural adaptation to the conversions of Muslims to Christianity in Indonesia. Since the 1960s, 6.5 million people have converted, and as of 2023, Christians make up 10.49 percent of the population. Findings show that urban-driven conversions and resilience strategies are similar, but there are differences between voluntary and structural incentives. Indonesian churches can use education, media, and worship that is based on local culture to help people feel like they belong and promote diversity. The research suggests a missiological-comparative framework for subsequent investigations, providing insights for interfaith policy and global Christian-Muslim relations.